PERANCANGAN MEDIA PROMOSI SAS CAFE AND RESTO SURABAYA SEBAGAI UPAYA MENINGKATKAN BRAND LOYALTY - Nurajizah, Nurajizah; Bahruddin, Muh; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2015)
Abstract: SAS Cafe and Resto is an undertaking engaged in the culinary in Surabaya East which has considerable potential. SAS Cafe and Resto has traditional features as there are gazebos made of gelugu wood so that rural atmosphere feels more real and is surrounded by paddy fields around the Cafe and Resto. With the potential that is owned by SAS Cafe and Resto, the culinary field in this enterprise is still lacking in terms of promoting its products. Promotional activities are very important to market a product/brand, so the brand remains and can do approach to customers through these promotional activities. Promotional activities carried out by SAS Cafe and Resto very less because until now, promotional activities carried out was just a promo event, social media and website, so typical and products from SAS Cafe and Resto not yet seen in any promotional media campaign that has been done up to this point. The problem is, although the advantages owned by SAS Cafe and Resto are big enough, but the drop in visitors due to lack of activity can happen promotion conducted by SAS Cafe and Resto and the lack of innovation in the promotion as well as a multitude of culinary business that sprung up in Surabaya who approach customers through promotional programs. Therefore, it takes some effort to maintain customer loyalty, one of them is designing the right promotion media and innovative that can increase brand loyaltyÂ SAS Cafe and Resto.Â Keywords: Design, Promotional Media, Brand Loyalty